DIETHYLENE GLYCOL BASED DEEP EUTECTIC SOLVENTS AND THEIR PHYSICAL PROPERTIES - IBRAHIM, Rusul Khaleel; HAYYAN, Maan; ALSAADI, Mohammed Abdulhakim; IBRAHIM, Shaliza; HAYYAN, Adeeb; HASHIM, Mohd Ali (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In this study, diethylene glycol (DEG), as a hydrogen bond donor (HBD), was mixed with three ammonium based salts, namely N,N-diethylethanolammnium chloride, tetra-n-butylammonium bromide and choline chloride, as well as two phosphonium based salts, namely benzyl-triphenylphosphonium chloride and methyltriphenylphosphonium bromide, to prepare five different deep eutectic solvents (DESs) series. The DESs freezing points and functional groups were investigated. In addition, the physical properties viscosity, density, conductivity and surface tension were determined as function of temperature in the particular temperature range of 293.15- 353.15 K. It is worth mentioning that all examined DESs were stable and in liquid phase at room temperature which emphasize their promising potential to be utilized as inexpensive environment-friendlier solvents. Owing to their low recorded freezing points and viscosities, DEG based DESs can be effortlessly processed without any further heating required in diverse industrial applications.